Vx-Na2TiOSiO4 MWNTs: Reduction of V5+ by electronegative oxygen and doping mechanism of V4+, formation and its hydrogen uptake. (1st February 2022) - Pian, Shan; Xu, Fangfang; Li, Rumin; Xiao, Youhong; Dong, Guojun; Su, Yu
Abstract: V-doped Na2 TiOSiO4 multiwalled nanotubes (Vx -Na2 TiOSiO4 MWNTs) were prepared by an effective hydrothermal process and were characterized by SEM, XRD, FT-IR, Raman, TEM, 51 V-ssNMR, 29 Si-ssNMR and XPS methods. The results showed that the change of V 5+ to V 4+ was attributed to the reduction of the electronegative oxygen derived from the dehydration of the absorbed hydroxyl, and in this process, new oxygen vacancies resulting from electronegative oxygen were generated. Different from traditional structures, doped vanadium (V 4+ ) replaced partly the position of titanium (Ti 4+ ), which made Si 4+ exist in two chemical coordination environments, Ti–O–Si and V–O–Si. The formation of Vx -Na2 TiOSiO4 MWNTs was attributed to a curling process, and the unique morphology makes them have large pore volume and surface area to adsorb hydrogen. It adsorbed 0.388 wt% hydrogen even at the temperature of 77 K and hydrogen pressure of 1 bar, such a result provides a promising strategy for designing practical hydrogen storage materials. Graphical abstract: Image 1 Highlights: Vx -Na2 TiOSiO4 MWNTs with a Q 0 structure was formed by curling nanosheet. V 5+ was reduced by electronegative oxygen leading to a decrease of zeta potential. The doped V 4+ partially replaced Ti 4+ made Si exist in two chemical environments. The unique morphology of the curling NTs improves the hydrogen storage capacity.